Energy Management System of Microgrid using Optimization Approach. Issue 9 (2022) - Sarda, Jigar S.; Lee, Kwang; Patel, Hirva; Patel, Nishita; Patel, Dhairya
Abstract: Microgrid technology can efficiently integrate a new practical way for large-scale application of grid-connected generation of renewable energy. An Energy Management System (EMS) in microgrid, is important for optimum use of the distributed energy resources in smart, protected, consistent, and synchronized ways. This paper discusses the management of Energy Storage System (ESS) connected in a microgrid with a solar array and control the battery discharge and charge operations with converter based on the necessity of the demand. Problem for one-day energy management of microgrid is discussed. This paper focuses on analyzing of heuristic and optimization approach for minimizing total variable electricity prize for clear and cloudy day. The output variables like power of PV, grid, ESS, and loads, grid voltage, ESS state of charge and price graphs are analyzed for each case. The MATLAB software is used for simulating this case study.